2008
DOI: 10.1007/s10750-008-9296-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple invasions of Europe by East Asian cobitid loaches (Teleostei: Cobitidae)

Abstract: While it has been widely suggested that freshwater fishes from East Asia invaded the western Palaearctic, details about this process are largely unknown. Here, using the cytochrome b gene, we evaluated the phylogenetic relationships of a small group of Eurasian primary freshwater fishes (Cobitidae), which are widely distributed and species rich in East Asia and Europe, with the purpose of inferring their invasion process of Europe from East Asia. Though phylogenetic relationships of cobitids were not well reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Tang et al. () suggested existence of cryptic species based on diverse morphological characteristics of C. sinensis (Chen ; Zhu ; Chen and Chen ), which apparently was supported by the genetic analyses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Tang et al. () suggested existence of cryptic species based on diverse morphological characteristics of C. sinensis (Chen ; Zhu ; Chen and Chen ), which apparently was supported by the genetic analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Tang et al. ). However, many studies suggested that species and genus must fulfil two criteria, monophyly and distinctness (Wiley ; Paterson ; Cracraft ; Gill et al.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was described by Tang et al [27]. Fragments containing the complete mtDNA cytochrome b gene were obtained by polymerase chain reaction (PCR) using primer sets L14724 and H15915 [15].…”
Section: Dna Extraction Amplification and Sequencingmentioning
confidence: 99%
“…The procedure was described by Tang et al (2008). Fragments containing the mtDNA cytochrome b gene were obtained by polymerase chain reaction (PCR) amplification using primer sets L14724 and H15915 (Xiao et al, 2001).…”
Section: Dna Extraction and Sequence Analysesmentioning
confidence: 99%